2017
DOI: 10.4102/sajpsychiatry.v23i0.959
|View full text |Cite
|
Sign up to set email alerts
|

A rapid appraisal of the status of mental health support in post-rape care services in the Western Cape

Abstract: Background: Despite the well-known impact of rape on mental health and the widespread problem of rape in South Africa, mental health services for rape victims are scant and not a priority for acute-phase services. Survivors encounter multiple mental health struggles in this period including adherence to the post-exposure prophylaxis drugs to prevent HIV and finding support from important others. We have little information on what mental health is provided, by whom and how it is integrated into the post-rape pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…For too long, forensic mental health has concerned itself largely with accused persons, to the relative neglect of complainants and survivors of crime, especially those who have been subjected to sexual violence. Many of these survivors have mental health issues, either pre-existing or consequent to the assaults, which are often left formally unaddressed (Abrahams & Gevers, 2017). This can impact their participation in court proceedings, of which courts need to be made aware.…”
Section: Resultsmentioning
confidence: 99%
“…For too long, forensic mental health has concerned itself largely with accused persons, to the relative neglect of complainants and survivors of crime, especially those who have been subjected to sexual violence. Many of these survivors have mental health issues, either pre-existing or consequent to the assaults, which are often left formally unaddressed (Abrahams & Gevers, 2017). This can impact their participation in court proceedings, of which courts need to be made aware.…”
Section: Resultsmentioning
confidence: 99%
“…Effective and accessible mental health care post-rape has been identified as a critical gap in point-of-care services for rape survivors in LMIC (Abrahams & Gevers, 2017 ; Keynejad et al, 2020 ). In South Africa, immediate crisis counselling is offered to rape survivors who attend post-rape services i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Thuthuzela Care Centres (TCCs) who in partnership with non-government organisations (NGOs) provide crisis counselling. The same NGO also offer rape survivors long-term supportive counselling (Abrahams & Gevers, 2017 ). A concerted effort to provide holistic care to rape survivors has been made in the last decade through Thuthuzela Care Centres (TCCs) which are one-stop service centres that provide comprehensive services to victims of gender-based violence (GBV), including rape.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly one-third of participants stated that they had not disclosed their sexual assault because they were financially dependent on the perpetrator. The prevalence of sexual assault can also be deduced from male perpetrator prevalence studies, which indicate that 28–35% of men report having committed a sexual assault [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in South Africa have confirmed that sexual victimization is strongly associated with PTSD, depression, and suicidal behavior [ 7 , 8 , 9 ]. Many victims seek formal mental health care to address the emotional distress of sexual assault and its adverse impact on relationships and academic and occupational functioning [ 1 ].…”
Section: Introductionmentioning
confidence: 99%